2022
DOI: 10.1159/000522341
|View full text |Cite
|
Sign up to set email alerts
|

The Proximal Tubule as the Pathogenic and Therapeutic Target in Acute Kidney Injury

Abstract: <b><i>Background:</i></b> In 2004, the term acute kidney injury (AKI) was introduced with the intention of broadening our understanding of rapid declines in renal function and to replace the historical terms of acute renal failure and acute tubular necrosis (ATN). Despite this evolution in terminology, the mechanisms of AKI have stayed largely elusive with the pathophysiological concepts of ATN remaining the mainstay in our understanding of AKI. <b><i>Summary:</i></… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 68 publications
1
13
0
Order By: Relevance
“…However, the continuous associations were inconsistent across all subclinical CVD outcomes that we evaluated, possibly as a result of nonlinear associations seen in the categorical analysis of A1 M. The intersection of kidney and heart health is a complex and incompletely understood pathway. The kidney tubules are a major site of water reabsorption and ion transport, which could modulate blood pressure and CVD risk [26]. Despite the limitations of its cross-sectional design, our study implicates kidney tubular dysfunction, independent of eGFR, as a part of the pathway between kidney disease and atherosclerotic CVD [12].…”
Section: Discussionmentioning
confidence: 73%
“…However, the continuous associations were inconsistent across all subclinical CVD outcomes that we evaluated, possibly as a result of nonlinear associations seen in the categorical analysis of A1 M. The intersection of kidney and heart health is a complex and incompletely understood pathway. The kidney tubules are a major site of water reabsorption and ion transport, which could modulate blood pressure and CVD risk [26]. Despite the limitations of its cross-sectional design, our study implicates kidney tubular dysfunction, independent of eGFR, as a part of the pathway between kidney disease and atherosclerotic CVD [12].…”
Section: Discussionmentioning
confidence: 73%
“…In the post-ischaemic kidney, tubular injuries can be either lethal as apoptosis and necrosis or sublethal as disintegrations in cytoskeleton and intercellular junctional proteins, detachment of viable cells, shedding of brush borders and formation of intratubular casts. 1,[21][22][23] The most drastic epithelial cell damages in both VIR and VIR-rRPP groups occurred in the PT and TAL, because of their high active transport, 24,25 and especially in the OM-os where is primarily supplied by venous blood of ascending vasa and with a hypoxic state even in the normal condition. 18,19,23 It has been shown that bilateral renal arterial clamping in the male spontaneously hypertensive rats (SHR) compared with the female SHR and normotensive male rats results in greater VC, especially in the OM, which is associated with the development of severer AKI and more delay in recovery of the post-ischaemic kidney.…”
Section: Discussionmentioning
confidence: 99%
“…GLUT5 has only been reported to be expressed in the S3 segment of the proximal tubule, which is located in the outer stripe of the outer medulla. 52 Thus, it seems unlikely that either GLUT2 or GLUT5 plays a critical role in fructose-induced saltsensitive hypertension. The current data show a lack of sexual dimorphism in the BP response between male and female wild-type rats with the increase in BP caused by FHS being similar.…”
Section: Discussionmentioning
confidence: 99%